Brain Lateralization in Mice Is Associated with Zinc Signaling and Altered in Prenatal Zinc Deficient Mice That Display Features of Autism Spectrum Disorder - Grabrucker, Stefanie; Haderspeck, Jasmin C.; Sauer, Ann Katrin; Kittelberger, Nadine; Asoglu, Harun; Abaei, Alireza; Rasche, Volker; Schön, Michael; Boeckers, Tobias M.; Grabrucker, Andreas M. (Frontiers in Molecular Neuroscience, 2018)
A number of studies have reported changes in the hemispheric dominance in autism spectrum disorder (ASD) patients on functional, biochemical and morphological level. Since asymmetry of the brain is also found in many vertebrates, we analyzed whether prenatal zinc deficient (PZD) mice, a mouse model with ASD like behavior, show alterations regarding brain lateralization on molecular and behavioral level. Our results show that hemisphere specific expression of marker genes is abolished in PZD mice on mRNA and protein level. Using magnetic resonance imaging (MRI), we found an increased striatal volume in PZD mice with no change in total brain volume. Moreover, behavioral patterns associated with striatal lateralization are altered and the lateralized expression of dopamine receptor 1 (DR1) in the striatum of PZD mice was changed. We conclude that zinc signaling during brain development has a critical role in the establishment of brain lateralization in mice.